Florbetapir (18F) for brain amyloid positron emission tomography: Highlights on the European marketing approval. (13th January 2014) - Cortes‐Blanco, Anabel; Prieto‐Yerro, Concha; Martinez‐Lazaro, Raul; Zamora, Javier; Jiménez‐Huete, Adolfo; Haberkamp, Marion; Pohly, Johannes; Enzmann, Harald; Zinserling, Jörg; Strassmann, Valerie; Broich, Karl
Abstract: Florbetapir ( 18 F) for brain amyloid positron emission tomography (PET) imaging has been recently approved in Europe to estimate β‐amyloid neuritic plaque density in the brain when the subject is still alive. Such density is one of the key issues for the definitive diagnosis of Alzheimer's disease (AD) at autopsy. This capability of florbetapir ( 18 F) is regarded as a significant improvement in the diagnostic procedures for adult patients with cognitive impairment who are being evaluated for AD and other causes of cognitive impairment. The current paper highlights the specific characteristics of the European marketing authorization of florbetapir ( 18 F).